Evaluation of the LPG 3 Kg Subsidy Program: how far has it Reached the Poor? - Hasanah, Uswatun; Haliah, Haliah; Kusumawati, Andi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Public service is a series of activities aimed at meeting the needs of the community in accordance with applicable laws and regulations. Every citizen and resident has the right to obtain goods, services, or administrative services provided by public service providers. The problem of poverty is an issue that must still be considered by a country, especially in developing countries such as Indonesia. This research aims to provide a deeper insight into the evaluation of the 3 kg LPG cylinder subsidy to ensure that the program is right on target and provides benefits for the poor, micro businesses, farmers and fishermen. This article uses a qualitative approach with a literature study analysis method. The result is that the 3 kg LPG subsidy program in Indonesia helps the poor, but there are still challenges in its implementation.